2008
DOI: 10.1186/1471-2296-9-29
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the MMSE in detecting cognitive impairment when administered by general practitioners: A prospective observational study

Abstract: Background: The Mini-Mental State Examination (MMSE) has contributed to detecting cognitive impairment, yet few studies have evaluated its accuracy when used by general practitioners (GP) in an actual public-health setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 42 publications
(32 reference statements)
2
66
0
4
Order By: Relevance
“…The test was administered in our study by a general practitioner who had received prior training on administration and interpretation of the MMSE. A study revealed a good interrater concordance (κ statistic = 0.86) between MMSE scores by general practitioners and neuropsychologists [11]. Since most of our study participants were illiterate and could express themselves neither in English nor French, some parts of the MMSE were translated to the Batibo language to ease administration.…”
Section: Methodsmentioning
confidence: 99%
“…The test was administered in our study by a general practitioner who had received prior training on administration and interpretation of the MMSE. A study revealed a good interrater concordance (κ statistic = 0.86) between MMSE scores by general practitioners and neuropsychologists [11]. Since most of our study participants were illiterate and could express themselves neither in English nor French, some parts of the MMSE were translated to the Batibo language to ease administration.…”
Section: Methodsmentioning
confidence: 99%
“…Relativamente às propriedades psicométricas, apresenta boa concordância entre os examinadores, alta fiabilidade teste-reteste (Pezzotti, Scalmana, Mastromattei, & Di Lallo, 2008), consistência interna moderada (Alfha de Cronbach de 0.464) (Morgado et al (2009), uma sensibilidade de 71-92%, uma especificidade de 56-96%, um valor preditivo positivo de 15-75% e um valor preditivo negativo de 95-99% (Adelman & Daly, 2005). Apesar da sua utilidade na avaliação tanto em níveis de gravidade moderada a severa ou na exclusão de comprometimento cognitivo encontrar-se bem documentada (Thibaut & Steiner, 2004), vários estudos refutam a importância da sua combinação com outros instrumentos (Mitchell, 2009).…”
Section: Mini-mental State Examination -Mmseunclassified
“…They were further classified into normal cognition, mild impairment, moderate impairment, and severe impairment based on their MMSE scores of 25-30, 20-25, 10-20, and 0-10, respectively [27], with each lower score indicating a need for greater supervision. MMSE is an instrument that has been proven to be effective in the screening of cognitive impairment in a general outpatient clinic setting [28]. MMSE has a sensitivity of 66% and a specificity of 99% in dictating cognitive decline [29].…”
Section: Methodsmentioning
confidence: 99%